The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2337/dc10-2145
|View full text |Cite
|
Sign up to set email alerts
|

Serum Carotenoids and Fat-Soluble Vitamins in Women With Type 1 Diabetes and Preeclampsia

Abstract: OBJECTIVEIncreased oxidative stress and immune dysfunction are implicated in preeclampsia (PE) and may contribute to the two- to fourfold increase in PE prevalence among women with type 1 diabetes. Prospective measures of fat-soluble vitamins in diabetic pregnancy are therefore of interest.RESEARCH DESIGN AND METHODSMaternal serum carotenoids (α- and β-carotene, lycopene, and lutein) and vitamins A, D, and E (α- and γ-tocopherols) were measured at first (12.2 ± 1.9 weeks [mean ± SD], visit 1), second (21.6 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 25 publications
3
58
1
Order By: Relevance
“…table 1) [32,33,34,35]. In the 5 published confounder-adjusted studies included in the analyses [16,17,30,35,36,37], 3 different 25(OH)D assays were used, and the threshold for low vitamin D status was defined as 37.5 nmol/l in 2 studies and 50 nmol/l in 3 studies.…”
Section: Resultsmentioning
confidence: 99%
“…table 1) [32,33,34,35]. In the 5 published confounder-adjusted studies included in the analyses [16,17,30,35,36,37], 3 different 25(OH)D assays were used, and the threshold for low vitamin D status was defined as 37.5 nmol/l in 2 studies and 50 nmol/l in 3 studies.…”
Section: Resultsmentioning
confidence: 99%
“…A number of investigators have recognized the potential role of vitamin D in preeclampsia (11, 13, 2332). For example, Xu et al (11) conducted a retrospective study investigating both maternal IL-6 levels and vitamin D levels in the third trimester.…”
Section: Role Of Vitamin D In Preeclampsiamentioning
confidence: 99%
“…However, abnormalities arising earlier in pregnancy are also of interest and could provide additional predictive and mechanistic insights (including reasons for elevation of endoglin). In this regard, we recently showed that lower levels of ␤-carotene early in pregnancy are associated with subsequent PE in T1DM women (15).…”
mentioning
confidence: 99%